The mediating role of anxiety in disease uncertainty and acute stress in acute ischaemic stroke patients in the post-epidemic era - Tan, Hui (Frontiers in Psychiatry, 2023)
Objective To analyse the influencing factors of anxiety, disease uncertainty and acute stress response in patients with acute ischaemic stroke, and to verify the mediating role of anxiety in the post-epidemic era. Methods 240 patients with acute ischaemic stroke were selected from a tertiary hospital in Wuhan City and investigated by questionnaire and convenience sampling methods. Results The total anxiety score, disease uncertainty and acute stress reaction were at moderate levels. Anxiety was positively correlated with illness uncertainty, and anxiety and acute stress response were negatively correlated. Multiple linear regression analysis showed that Sickness uncertainty, acute stress response, age, and work status influenced anxiety. Anxiety mediated the prediction of Sickness uncertainty and acute stress response, with the mediating effect accounting for 35.6% of the total effect. Conclusion Disease uncertainty in patients with acute ischaemic stroke in the post-epidemic era directly affects the acute stress response and indirectly through anxiety.